2011
DOI: 10.1029/2010ja015825
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation of NOxfrom the lower thermosphere to the upper stratosphere in the years 1991-2005

Abstract: [1] The interannual variation of NO x throughout the year is investigated for the period 1991-2005 at middle to high latitudes using Halogen Occultation Experiment (HALOE) on UARS measurements. We find a clear correlation of NO x between 80 and 130 km with the auroral electrojet index in both hemispheres, which is fairly independent of season, indicating a relatively frequent NO x source from precipitating auroral electrons of energies ranging from about 1 keV to several tens of keV. Between 80 and 100 km, NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 36 publications
(54 reference statements)
1
50
0
Order By: Relevance
“…They then used a chemistry general circulation model to simulate surface temperature response to geomagnetic activity variations by realistically varying the A p index to further explore the mechanisms leading to the temperature responses reported earlier by Rozanov et al [2005]. The A p -driven NO x parameterization that they used in their model had previously proved to be realistic and in a good agreement with observations [Baumgaertner et al, 2009], concurring well with earlier observations of the relationship between polar middle atmosphere NO x concentrations and the variation in geomagnetic activity and particle precipitation [Siskind et al, 2000;Randall et al, 2007;Seppälä et al, 2007;Sinnhuber et al, 2011]. Baumgaertner et al [2011] showed the temperature response from 0.01 hPa to 1000 hPa (mesopause to surface) when the model was forced with the A p -controlled EPP-NO x (their Figure 9).…”
Section: Introductionsupporting
confidence: 71%
“…They then used a chemistry general circulation model to simulate surface temperature response to geomagnetic activity variations by realistically varying the A p index to further explore the mechanisms leading to the temperature responses reported earlier by Rozanov et al [2005]. The A p -driven NO x parameterization that they used in their model had previously proved to be realistic and in a good agreement with observations [Baumgaertner et al, 2009], concurring well with earlier observations of the relationship between polar middle atmosphere NO x concentrations and the variation in geomagnetic activity and particle precipitation [Siskind et al, 2000;Randall et al, 2007;Seppälä et al, 2007;Sinnhuber et al, 2011]. Baumgaertner et al [2011] showed the temperature response from 0.01 hPa to 1000 hPa (mesopause to surface) when the model was forced with the A p -controlled EPP-NO x (their Figure 9).…”
Section: Introductionsupporting
confidence: 71%
“…As the photochemical lifetime of NO x is in the range of weeks to months during polar winter, NO x from the upper mesosphere and lower thermosphere can reach down far into the stratosphere. Enhanced values of mesospheric and stratospheric NO x attributed to auroral production or geomagnetic activity have been observed sporadically in polar winters for many decades (Solomon et al, 1982;Siskind et al, 2000;Randall et al, 2007;Sinnhuber et al, 2011). However, these observations were mostly limited to sunlit areas, and thus did not observe deep into polar night.…”
mentioning
confidence: 73%
“…citation, and dissociation of the most abundant species, N 2 and O 2 , and subsequent ion chemistry (M. Sinnhuber et al, 2012). Both HO x (H, OH) and NO x (N, NO, NO 2 , NO 3 ) contribute to catalytic ozone loss in the middle atmosphere, HO x mainly in the mesosphere (above ≈ 1 hPa), and NO x mainly in the stratosphere (below ≈ 1 hPa) (Lary, 1997).…”
mentioning
confidence: 99%
“…In Fig. 1 different proxies for energetic particle precipitation for this time are shown: the Ap index as an indicator of geomagnetic activity; a merged data set of electron fluxes from the POES instrument combining two upward-looking channels to derive 100-300 keV precipitating electrons as described in Sinnhuber et al (2011); and proton fluxes as measured in geostationary orbit by the particle counters onboard GOES-10. Both Ap index and proton fluxes are available online from the National Geophysical Data Center (NGDC; spidr.ngdc.noaa.gov/spidr).…”
Section: Solar and Geomagnetic Activitymentioning
confidence: 99%
“…Verronen et al (2011) have shown a direct impact of energetic electron precipitation on the OH abundance above 70 km altitude during two large geomagnetic storms in March 2005 and April 2006, with smaller contributions down to 50 km during one event. Sinnhuber et al (2011) have used a long-term data set of NO x measurements (NO+NO 2 ) from HALOE/UARS from 1991 to 2005 to investigate the direct impact of energetic electron precipitation onto the middle atmosphere. Their study also shows a direct contribution from electrons mainly above 80 km, with smaller and rather sporadic contributions to lower altitudes.…”
Section: Introductionmentioning
confidence: 99%